Perancangan Sistem Informasi Penjualan Berbasis Website Pada Zulfa Kochenk Oren Catshop Dengan Metode Waterfall - Anton Siregar; M. Samsul Aripin; Sandi Tamalia Herman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Zulfa Kochenk Oren Catshop which is located in Parung Panjang is a business sector engaged in the sale of equipment, as well as pet food, especially cats. Zulfa Kochenk Oren Catshop in conducting marketing and sales still uses a simple system, one example is social media which raises several obstacles, namely the small scope of product marketing and is not well known by the public. With the rapid development of technology in this industrial field, it creates very innovative ideas in various ways such as sales, marketing, and so on. This research found a problem which still uses a manual sales system. Therefore, by using the Waterfall method, researchers try to analyze and implement a website-based sales system that is connected to a database so that everything runs more easily, and buyers will be served faster when they want to buy.